1967
DOI: 10.1002/aja.1001200312
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms in blood glucose and the effect of different lighting schedules, hypophysectomy, adrenal medullectomy and starvation

Abstract: With other environmental factors rigidly standardized, normal SpragueDawley rats were maintained under the following lighting schedules: (1) LD 12:12, artificial light from 6:OO A.M. to 6:OO P.M. alternating with 12 hours of darkness; (2) DL 12:12, reversal of the first schedule; (3) DD, constant darkness; and ( 4 ) LL. constant illumination.During each lighting regimen, blood glucose levels were determined on separate subgroups of 11 to 18 animals at bi-hourly intervals during a 24-hour period. Significant ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
3
1

Year Published

1972
1972
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(30 citation statements)
references
References 9 publications
4
22
3
1
Order By: Relevance
“…A clear circadian variation is seen in the blood glucose level in normal mice. The peak position in our experiment is found 4 hrs later than the peak position found in rats (Pauly et al, 1967). This différence can be attributed to species différences or, alternatively, to différences in the method of standardization which, probably, produces différent feeding patterns in animais caged in groups of two per cage, as is the case in thèse experiments and in the single caged animais of the présent experiments (Vilchez et al, 1971).…”
Section: Resultscontrasting
confidence: 41%
See 1 more Smart Citation
“…A clear circadian variation is seen in the blood glucose level in normal mice. The peak position in our experiment is found 4 hrs later than the peak position found in rats (Pauly et al, 1967). This différence can be attributed to species différences or, alternatively, to différences in the method of standardization which, probably, produces différent feeding patterns in animais caged in groups of two per cage, as is the case in thèse experiments and in the single caged animais of the présent experiments (Vilchez et al, 1971).…”
Section: Resultscontrasting
confidence: 41%
“…The existence of circadian variations in blood glucose has been repeatedly reported (for review see Pauly et al, 1967), but very few observations hâve been made in mice ) and we hâve not found références to circadian variations in blood glucose in hepactomized animais.…”
Section: Introductioncontrasting
confidence: 52%
“…Studies in humans and rodents have shown an alteration in both plasma glucose and insulin concentrations and variation in sensitivity of tissues to insulin over a 24-h light/darkness period. For example, humans have a higher glucose output and insulin requirement in the early morning hours (Carroll & Nestel 1973, Lee et al 1992, whereas rodents have higher concentrations of glucose and insulin in the dark period compared with the light period (Pauly & Scheving 1967), which may be associated with the initiation of physical activity (La Fleur 2003): it is important to recognise that rodents are nocturnally active and circulating insulin and glucose concentrations are higher during the dark phase (Pauly & Scheving 1967). Similarly, diurnal fluctuations in the actions of the D 2 dopamine receptor agonist bromocryptine on insulin sensitivity have been observed, with increased sensitivity in the morning and suppression in hepatic glucose production in the afternoon (Luo et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The alteration in hepatic glucose formation is consistent in phase with the serum cortisol cycle, but is said to survive, at least in part, adrenalectomy and hypophysectomy (63). It may be light-mediated (71). It may reflect multifactorial variation in hepatic gluconeogenetic enzymes (72)(73)(74) coordinated with respect to time in some unknown way by the hypothalamus (74).…”
Section: Possible Reasons For the Diversity Of Findings In The Pastmentioning
confidence: 98%